2022
DOI: 10.1038/s41416-022-01737-2
|View full text |Cite
|
Sign up to set email alerts
|

First-line trifluridine/tipiracil + bevacizumab in patients with unresectable metastatic colorectal cancer: final survival analysis in the TASCO1 study

Abstract: Background Therapeutic options are limited in patients with unresectable metastatic colorectal cancer (mCRC) ineligible for intensive chemotherapy. The use of trifluridine/tipiracil plus bevacizumab (TT-B) in this setting was evaluated in the TASCO1 trial; here, we present the final overall survival (OS) results. Methods TASCO1 was an open-label, non-comparative phase II trial. Patients (n = 153) were randomised 1:1 to TT-B (trifluridine/tipiracil 35 mg/m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Several clinical trials have already been conducted to investigate the benefit of this combination therapy in the beginning of treatment for patients with mCRC, especially older patients who are not suitable for intensive chemotherapy. The phase II TASCO1 study evaluated the efficacy and safety of TAS-102 plus BEV compared with capecitabine plus BEV as first-line therapy in patients who were unsuitable for intensive chemotherapy, which showed that TAS-102 combined with BEV had promising clinical activity and a tolerable safety profile ( 21 ). Furthermore, in the KSCC1602 study, the combination was effective in the first-line treatment of elderly patients (ORR 40.5%, DCR 86.5%) ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials have already been conducted to investigate the benefit of this combination therapy in the beginning of treatment for patients with mCRC, especially older patients who are not suitable for intensive chemotherapy. The phase II TASCO1 study evaluated the efficacy and safety of TAS-102 plus BEV compared with capecitabine plus BEV as first-line therapy in patients who were unsuitable for intensive chemotherapy, which showed that TAS-102 combined with BEV had promising clinical activity and a tolerable safety profile ( 21 ). Furthermore, in the KSCC1602 study, the combination was effective in the first-line treatment of elderly patients (ORR 40.5%, DCR 86.5%) ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of trifluridine-tipiracil and bevacizumab has also been studied in the first-line setting in both the phase III SOLSTICE study 296 and the phase II TASCO1 study. 297,298 Both of these studies compared trifluridine-tipiracil plus bevacizumab to capecitabine plus bevacizumab in patients who were not candidates for intensive therapy and have shown similar OS and PFS results between the 2 treatment groups. Based on concerns about the hematologic and financial toxicities with trifluridinetipiracil compared with capecitabine, the NCCN Panel does not currently recommend trifluridine-tipiracil, with or without bevacizumab, as first-line therapy for mCRC.…”
Section: Trifluridine-tipiracil (Tas-102)mentioning
confidence: 99%
“…She declined further treatment with this regimen. Pursuant to her goals of minimizing time spent at the cancer center and using the least toxic regimen, she was transitioned to treatment with trifluridine/tipiracil plus bevacizumab in January 2021[ 3 ]. Imaging revealed treatment response with subsequent progression in November 2021, eleven months after initiation of treatment.…”
Section: Treatmentmentioning
confidence: 99%